Un frailty aditivo en modelos de supervivencia bivariante - Navarrete Álvarez, Esteban (1999)
Bivariate survival models based on the presence of an unobseved random covariate, grailty, tend to assume a proportional hazard hypothesis. A bivariate survival model is constructed. It is based on frailty model that acts additivelky on the hazard function.